PRODUCTION AND EVALUATION OF ETHANOL FROM COFFEE PROCESSING BY-PRODUCTS - NAVIA P., Diana P.; VELASCO M., Rinaldo de J.; HOYOS C., José L. (Vitae, 2011)
Currently, many research studies are being carried out on the production of alcohol from lignocellulosic biomasses. In this study, the ethanol obtained from a mixture of coffee pulp and mucilage, commercial baker’s yeast and panela (dehydrated and solidified cane juice) was evaluated. The pulp and mucilage of coffee underwent an acid hydrolysis, and the wort (pulp juice and mucilage) was fermented with an inoculum of exponential phase Saccharomyces cerevisiae and commercial whole panela. The fermented product was distilled, and the gas chromatographic analysis showed an ethanol yield of 25.44 kg/m3, resulting from the 64.40 kg/m3 of total sugars, such yield is equivalent to 77.29% of the theoretical yield. This fact shows that the production of ethanol is viable in small coffee farms using readily available raw materials. The stillage was analyzed and it presented the following values: 0.40 ppm (Iron), 0.97 ppm (Magnesium), 1.54 ppm (Calcium), and 4.40 ppm (Phosphorus). The results confirm that they are particularly useful as a complement in the production of bio-fertilizers for earthworms.